Intelligent sensor : machine prognostics on a chip - Lim, Teck Yian. (2010)
Failures of vital factory equipment are often the reason for production stoppages and a regular maintenance schedule is required to ensure proper operation of all factory equipment. However, these method of maintenance can be both costly and inefficient. Vibrations are present in all machinery with moving parts and it had always been regarded as an indicator of the health and condition of rotating machinery. With advances in technology, what used to be a mechanic's hunch can now be measured and accurately. While sensing technologies and processing methods exist, they are often developed and deployed separately. Fortunately, recent advancements in sensing, signal processing and wireless communication technologies, it becomes possible to deploy sensors in critical areas of interest. This project is a proof-of-concept implementation of intelligent sensor nodes capable of processing and analyzing vibration signals from a MEMS sensor. In addition to implementing signal processing algorithms on the wireless sensor node, special design considerations were also made to allow the wireless sensor node to be reconfigurable and modular.